2020
DOI: 10.48550/arxiv.2010.02645
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multirotors from Takeoff to Real-Time Full Identification Using the Modified Relay Feedback Test and Deep Neural Networks

Abstract: Low cost real-time identification of multirotor unmanned aerial vehicle (UAV) dynamics is an active area of research supported by the surge in demand and emerging application domains. Such real-time identification capabilities shorten development time and cost, making UAVs' technology more accessible, and enable a variety of advanced applications. In this paper, we present a novel comprehensive approach, called DNN-MRFT, for real-time identification and tuning of multirotor UAVs using the Modified Relay Feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The model structures used for identification were proposed by [28] and confirmed experimentally in [22], [29], [31]. The vertical motion dynamics (i.e.…”
Section: B Linearized and Loosely Coupled Modelsmentioning
confidence: 83%
“…The model structures used for identification were proposed by [28] and confirmed experimentally in [22], [29], [31]. The vertical motion dynamics (i.e.…”
Section: B Linearized and Loosely Coupled Modelsmentioning
confidence: 83%
“…This work further develops the controller tuning approach presented in [18] for state estimation. We showed that the SISO models used for channel wise parameter identification is able to capture the dynamics of the UAV presented in literature.…”
Section: Discussionmentioning
confidence: 99%
“…Note that we have omitted the yaw moment as estimation of the yaw dynamics is not of interest in this work, where the focus is devoted to fast transient dynamics that are present in aggressive maneuvers. Moreover, control and estimation for yaw dynamics is simpler due to the presence of full state measurements and the lower relative degree of the system [18]. Therefore in this work we are using a kinematic estimator for the yaw states based on [1].…”
Section: B Linearized and Loosely Coupled Modelsmentioning
confidence: 99%
See 2 more Smart Citations